Comparison of two radiofrequency-based hemostatic devices: saline-linked bipolar vs. cooled-electrode monopolar - Moll, Xavier (2022)
Purpose: To characterize the coagulation zones created by two radiofrequency (RF)-based hemostatic devices: one comprised an internally cooled monopolar electrode and the other comprised externally irrigated bipolar electrodes (saline-linked). Materials and methods: RF-induced coagulation zones were created on ex vivo and in vivo porcine models. Computer modeling was used to determine the RF power distribution in the saline-linked device. Results: Both external (irrigation) and internal cooling effectively prevented tissue sticking. Under ex vivo conditions in ‘painting’ application mode, coagulation depth increased with the applied power: 2.8 − 5.6 mm with the 3-mm monopolar electrode, 1.6 − 6.0 mm with the 5-mm monopolar electrode and 0.6 − 3.2 mm with the saline-linked bipolar electrodes. Under in vivo conditions and using spot applications, the 3-mm monopolar electrode created coagulation zones of similar depth to the saline-linked bipolar electrodes (around 3 mm), while the 5-mm monopolar electrode created deeper coagulations (4.5 − 6 mm) with less incidence of popping. The presence of saline around the saline-linked bipolar electrodes meant that a significant percentage of RF power (50 − 80%) was dissipated by heating in the saline layer. Coagulation zones were histologically similar for all the tested devices. Conclusions: Both external (irrigation) and internal cooling in hemostatic RF devices effectively prevent tissue sticking and create similar coagulation zones from a histological point of view. Overall, saline-linked bipolar electrodes tend to create shallower coagulations than those created with an internally cooled monopolar electrode.